Amperometric detection of dopamine on Prussian blue nanocube-decorated electrochemically reduced graphene oxide hybrid electrode. (2021) - Eryiğit, Mesut; Gür, Eftade Pınar; Hosseinpour, Mohammad; Özer, Tuba Öznülüer; Doğan, Hülya Öztürk
Abstract: The purpose of this study is to fabricated a novel Prussian blue (PB)-decorated electrochemically reduced graphene oxide (ERGO) hybrid film (ERGO/PB) by electropolymerization of PB onto the ERGO-modified Au electrode, and to discuss the electrocatalytic activity of ERGO/PB for DA sensor. The ERGO/PB nanocomposite for DA biosensor exhibited a higher catalytic effect (linear range from 0.01 mM to 10.0 mM and detection limit of 0.02 µM at a signal-to-noise ratio of 3) than the naked Au, ERGO-modified Au, and PB-modified Au electrodes. This ERGO/PB nanocomposite-modified electrode provided a novel, simple, and low-cost route for the electrooxidation of DA.